Flavor precursor formation of non-fermented forastero cocoa beans after flavourzyme® and glucose treatment - Tamimi, Kika Al; Hidayat, Chusnul; Utami, Tyas; Witasari, Lucia Dhiantika (Academic Press, 2023)
The chocolate flavor determines the quality of cocoa. Efforts have been made to enhance chocolate flavor, apart from fermentation, by adding aroma precursor-forming ingredients such as amino acids and reducing sugars to cocoa nibs. This study aimed to determine the effect of protease from Aspergillus oryzae (Flavourzyme®) and glucose toward flavor precursor formation in non-fermented cocoa nibs. First, the highest Flavourzyme® concentration and the optimal incubation time to hydrolyze protein in non-fermented cocoa nibs were determined. Then, the non-fermented cocoa nibs were treated with Flavourzyme®, glucose, and the combination of both. Afterward, cocoa nibs were dried and tested for their pH, fermentation index, and the contents of reducing sugar and free amino acids. The present results suggested that the highest degree of hydrolysis was obtained from treatment with 50 U/g Flavourzyme® in 8 h of incubation time. Flavourzyme® could reduce the pH of non-fermented cocoa beans to pH 5.8. Cocoa nibs treated with Flavourzyme® and glucose showed higher fermentation index, and reducing sugar content than naturally fermented cocoa nibs. Furthermore, the free hydrophobic amino acids (Tyr, Phe, Leu) were in the highest level. Thus, Flavourzyme® and glucose treatment could enhance the precursor flavor in non-fermented cocoa nibs. © 2023